2001
DOI: 10.1074/jbc.m102638200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the Constitutive Activity of Estrogen-related Receptor α-1

Abstract: Based on ligand binding properties, nuclear receptors can be classified into three types. The first type of nuclear receptor, including estrogen receptor (ER) 1 and androgen receptor, is activated by specific ligands. The second type of receptor, similar to steroid and xenobiotic receptor, has a wide selectivity for ligands. The third type of receptor, like ERR␣-1, is transcriptionally active in the absence of exogenous ligand. The third type of receptor has similar structural domain arrangements to the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 10 publications
2
51
0
Order By: Relevance
“…Furthermore, whereas ERs are ligand-activated receptors, ERRs are constitutively active (13)(14)(15)(16), and a structural study confirmed that the ERR␥ LBD can adopt a transcriptionally active conformation and interact with the steroid receptor coactivator 1 (SRC-1) in the absence of any ligand (12). Together, these observations suggest that ERRs are ligand-independent activators of transcription whose activation potential may rather be determined by the presence of transcriptional coactivators (17)(18)(19)(20).…”
mentioning
confidence: 72%
“…Furthermore, whereas ERs are ligand-activated receptors, ERRs are constitutively active (13)(14)(15)(16), and a structural study confirmed that the ERR␥ LBD can adopt a transcriptionally active conformation and interact with the steroid receptor coactivator 1 (SRC-1) in the absence of any ligand (12). Together, these observations suggest that ERRs are ligand-independent activators of transcription whose activation potential may rather be determined by the presence of transcriptional coactivators (17)(18)(19)(20).…”
mentioning
confidence: 72%
“…In all three instances, we have demonstrated that mutations at relevant H3 and H5 positions markedly alter receptor sensitivity and͞or specificity, allowing us to create gain-of-function mutations for each of these receptors. Furthermore, an estrogen receptor ␣ bearing a substitution of phenylalanine for alanine at this precise H3 residue is constitutively active (23). Whereas loss-of-function mutations in NRs are relatively easy to devise, mutations which increase receptor activity are rare.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a phenylalanine residue (Phe 328 on H3) in the ligand binding pocket (LBP) has been found to be essential for the constitutive activity of ERR␣, because its mutation to alanine abolishes constitutive activity (10). However, alanine residues are found at the corresponding positions of ERR␤ and ERR␥, indicating either different structural reasons for the apparent constitutive activity or a different mode of regulation for these other ERR isotypes.…”
mentioning
confidence: 88%
“…2B)). Phe 328 has been found to be crucial for the constitutive activity of ERR␣ (10). The substitutions Phe 382 /Tyr 326 and Gly 402 /Asn 346 do not significantly open the bottom part of the ERR␣ LBP with respect to ERR␥, because as a compensation the ERR␣ residues Phe 382 , Ala 393 , Gly 402 , and Leu 405 move closer together and thus practically fill the otherwise empty space.…”
Section: Structure Determination Of the Complex Between Err␣ Lbdmentioning
confidence: 99%